2006
DOI: 10.1161/circulationaha.105.543678
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Posterolateral Scar Tissue on Clinical and Echocardiographic Improvement After Cardiac Resynchronization Therapy

Abstract: Background-Currently, one third of patients treated with cardiac resynchronization therapy (CRT) do not respond.Nonresponse to CRT may be explained by the presence of scar tissue in the posterolateral left ventricular (LV) segments, which may result in ineffective LV pacing and inadequate LV resynchronization. In the present study, the relationship between transmural posterolateral scar tissue and response to CRT was evaluated. Methods and Results-Forty consecutive patients with end-stage heart failure (NYHA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
447
4
25

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 721 publications
(495 citation statements)
references
References 28 publications
19
447
4
25
Order By: Relevance
“…This has become an active area of research in the CRT setting, with several subsequent studies documenting the value of scar burden, location and transmurality of myocardial infarctions as a predictor of response to CRT [20-24]. Consistent with this work, our study showed myocardial infarction and scar burden (as determined by percentage of LGE mass) to portend an adverse response to CRT.…”
Section: Discussionsupporting
confidence: 86%
“…This has become an active area of research in the CRT setting, with several subsequent studies documenting the value of scar burden, location and transmurality of myocardial infarctions as a predictor of response to CRT [20-24]. Consistent with this work, our study showed myocardial infarction and scar burden (as determined by percentage of LGE mass) to portend an adverse response to CRT.…”
Section: Discussionsupporting
confidence: 86%
“…The location of scar is of equal importance, in particular when it is located in the posterolateral region of the LV, a site empirically thought to be optimal for LV lead deployment. Scar in this area is associated with lower response rates following CRT [45,48]. …”
Section: Tissue Characterizationmentioning
confidence: 99%
“…All coronary vein images were obtained during the systolic rest period when coronary veins are maximally dilated (4). This optimal trigger time was visually determined using a breath-hold 2D cine SSFP image in two-chamber orientation with the following imaging parameters: TE ϭ 1.3 ms, TR ϭ 2.6 ms, ␣ ϭ 60°, field of view (FOV) of 320 ϫ 320 ϫ 8 mm 3 , spatial resolution of 2 ϫ 2 ϫ 8 mm 3 , a temporal resolution of 21 ms and a total duration of 10.2 s. The trigger time was then visually selected as the onset of the least-motion period in the cross-section of coronary sinus.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, knowledge of coronary vein anatomy in relation to the tissue characteristics of the underlying myocardium in the pacing sites could improve the efficacy of this therapy, thereby improving on the 30 -40% nonresponder rate (1,2). It has been shown recently that CRT does not reduce LV dyssynchrony in patients with transmural scar tissue in posterolateral LV segments, resulting in clinical nonresponse to CRT (3).…”
mentioning
confidence: 99%